Efektivitas Program SADARI terhadap Pemahaman Caregiver dalam Dukungan Kemandirian Anak Usia 5–7 Tahun : The Effectiveness of the SADARI Program on Caregiver Understanding in Supporting the Independence of Children Aged 5–7 Years - Evi Noviyanti; Farida Kurniawati (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Independence is a crucial developmental task for children aged 5–7 years and requires caregiver support. However, caregivers' limited understanding often hinders optimal support for child independence. Therefore, structured training is needed to improve caregivers' understanding of child independence support. This study used a one-group pretest–posttest design with 13 caregivers. The intervention, in the form of SADARI (Sadar Dukung Anak Mandiri) training, was conducted face-to-face in four sessions, covering the concept of child independence, the role of caregivers, and practical strategies through the BICARA approach. Caregivers' understanding was measured before and after the intervention using an adaptation of the Vineland Social Maturity Scale (Doll, 1965). Data were analyzed using paired samples t-tests and Wilcoxon Signed-Rank tests to determine differences in pre-test and post-test scores. There was a significant increase in caregiver understanding scores between post-test and post-test 1 (t(13) = ?4.59; p < .001; Wilcoxon p = .003), and between post-test and post-test 2 (t(13) = ?3.24; p = .006; Wilcoxon p = .008). Descriptively, the average understanding score increased from 105 in the post-test to 117 in post-test 1 and 121 in post-test 2. Although scores fluctuated for some individuals, observations and quiz evaluations showed that the majority of caregivers understood the concept of child independence, the BICARA strategy, and their role in daily caregiving practices. SADARI training was proven effective in improving caregivers' cognitive understanding of how to support the independence of children aged 5–7 years. However, this increase was still limited to understanding and was not fully reflected in caregiving practices, which were influenced by caregiving experience and required further guidance to encourage changes in caregiver behavior.